Tick gut barriers impacting tick–microbe interactions and pathogen persistence. Issue 5 (6th October 2021) - Kitsou, Chrysoula; Foor, Shelby D.; Dutta, Shraboni; Bista, Sandhya; Pal, Utpal
Abstract: Ticks are regarded as one of the most ancient, unique, and highly evolved ectoparasites. They can parasitize diverse vertebrates and transmit a number of widespread infections. Once acquired from infected hosts, many tick‐borne pathogens, like Borrelia burgdorferi, are confined within the tick gut lumen and are surrounded by discrete gut barriers. Such barriers include the peritrophic membrane (PM) and the dityrosine network (DTN), which are in close contact with resident microbiota and invading pathogens, influencing their survival within the vector. Herein, we review our current state of knowledge about tick–microbe interactions involving the PM and DTN structures. As a model, we will focus on Ixodes ticks, their microbiome, and the pathogen of Lyme disease. We will address the most salient findings on the structural and physiological roles of these Ixodes gut barriers on microbial interactions, with a comparison to analogous functions in other model vectors, such as mosquitoes. We will distill how this information could be leveraged towards a better understanding of the basic mechanisms of gut biology and tick–microbial interactions, which could contribute to potential therapeutic strategies in response to ticks and tick‐borne infections. Abstract : Most tick‐borne pathogens, such as the Lyme disease spirochetes (black circle), are acquired within the tick gut along with the host‐derived blood meal. Acellular gut barriers like peritrophic membrane (solid blue line) and dityrosine network (green dotted line) in tick gut potentially cover the gut epithelial cells and physically separate them from the lumen, ultimately influencing the persistence of many tick‐borne pathogens. This review highlights our current state of knowledge about tick–microbe interactions involving these gut barriers. This image was created using BioRender (https://biorender.com/ ).